Characterization of a novel zinc transporter ZnuA acquired by Vibrio parahaemolyticus through horizontal gene transfer - Liu, Ming; Yan, Meiying; Liu, Lizhang; Chen, Sheng (Frontiers in Cellular and Infection Microbiology, 2013)
Vibrio parahaemolyticus is a clinically important foodborne pathogen that causes acute gastroenteritis worldwide. It has been shown that horizontal gene transfer (HGT) contributes significantly to virulence development of V. parahaemolyticus. In this study, we identified a novel znuA homolog (vpa1307) that belongs to a novel subfamily of ZnuA, a bacterial zinc transporter. The vpa1307 gene is located upstream of the V. parahaemolyticus pathogenicity island (Vp-PAIs) in both tdh-positive and trh-positive V. parahaemolyticus strains. Phylogenetic analysis revealed the exogenous origin of vpa1307 with 40% of V. parahaemolyticus clinical isolates possessing this gene. The expression of vpa1307 gene in V. parahaemolyticus clinical strain VP3218 is induced under zinc limitation condition. Gene deletion and complementation assays confirmed that vpa1307 contributes to the growth of VP3218 under zinc depletion condition and that conserved histidine residues of Vpa1307 contribute to its activity. Importantly, vpa1307 contributes to the cytotoxicity of VP3218 in HeLa cells and a certain degree of virulence in murine model. These results suggest that the horizontally acquired znuA subfamily gene, vpa1307, contributes to the fitness and virulence of Vibrio species.